Manajemen Kinerja Organisasi Perguruan Tinggi Swasta untuk Meningkatkan Mutu Lulusan - Nasrullah (Prodi Pendidikan Agama Islam STIT Al-Khairiyah Cilegon, 2017)
The current condition of tertiary institutions has been a mismatch between college graduates and the qualifications needed by the industry and services sectors in the community, resulting in problems when the graduates want to find work. The problems studied related to the Tri-Dharma Higher Education include education/teaching, research/development, and community service with a focus on problems in the performance of higher education organizations to produce quality and professional human resources. The purpose of this study is to describe the performance management of private higher education organizations in three Al-Khairiyah Colleges in Cilegon. This study uses a qualitative approach with descriptive methods. Data collection procedures through interview, observation and documentation study techniques. Theories studied include performance management, organizational theory and quality management. The discussion uses methods: SWOT analysis, BSC (Balanced Score Card), and TQM approach. The results of the study concluded: (1) Management of PTS organizational performance was well implemented. (2) PTS organizational performance strategy is going according to plan. (3) Supporting and inhibiting factors of PTS organizational performance are well considered by the leadership. (4) Efforts to improve the qualifications of teaching staff and education staff run well. Recommendations in the study are: (1) For foundations, they must give full autonomy and trust rights to the leaders of higher education institutions to carry out independent and professional management of higher education institutions. (2) For the leaders of private tertiary institutions, to improve the management of organizational performance which includes: planning, implementing and evaluating. leaders of private tertiary institutions, as well as optimizing the implementation of the tri dharma of tertiary institutions. (3) For lecturers, who have not shown good performance are given direct guidance. (4) For other researchers, can develop the concept of performance management of private higher education organizations.